Analysis and Enhancement of a Watermarking Protocol Suitable for Web Context - 曾鹏 曹珍富 林煌 (Shanghai jiao tong da xue xue bao, 2010)
A buyer-seller watermarking protocol is a combination of traditional watermarking and fingerprinting techniques. Recently, Frattolillo proposed such a watermarking protocol suitable for web context. Frattolillo＇s scheme has two problems which would make it hard to implement practically. Several possible solutions to the two problems are presented in this paper.